2002
DOI: 10.1515/bmte.2002.47.s1b.912
|View full text |Cite
|
Sign up to set email alerts
|

PERFUSION-CONTRACTILITY MATCHlNG DURING FONTAN CIRCULATION

Abstract: We investigated the relationship between coronary perfusion pressure (CPP) and myocardial contractility and the effects of an acute elevation of right atrial pressure (RAP) on this relationship in an experimental model of Fontan circulation in 6 anesthetized open-chest dogs with isolated perfused coronary arteries. The relationship between CPP and Ees could be described by biphasic J-shaped curves which were nearly identical before and under Fontan circulation. While above a "critical" CPP (72 +/- 9 mmHg vs. 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…ii. Approaches for handling of venous coronary flow, which drains into the RA, were analyzed and classified into two groups depending on whether the main PA was Mean (SD): 22.4 (1.5) Nawa et al 12 Mean (SD): 10.6 (1.75) Szabo et al 13 No data Szabo et al 14 Mean (SD): 22.3 (5.2) Tanoue et al 15 Mean (SD): 16.8 (2.7) Ovine Gandolfo et al 16 Range: 42.0-48.0 Koçyıldırım et al 17 Mean (SD): 65.0 (4.1) Myers et al 18 Mean (SD): 7.2 (1.1) Riemer et al 19 Range: 42.0-48.0 Rodefeld et al 20 Mean: 56.5; range: 33.0-78.6 Rodefeld et al 21 Mean (SD): 5.6 (1.5) Swartz et al 22 Mean (SD): 56.6 (5.7) Tsuda et al 23 Range: 47.0-57.0 Wang et al 24 Range: 35.0-45.0 Wang et al 25 Range: 35.0-45.0 Wang et al 26 Range: 35.0-45.0 Porcine Derk et al 27 Mean:50.7; range 44.0-61.0 Kanakis et al 28 Mean (SD): 43.0 (3.8) Klautz et al 29 Mean (SD): 28.3 (7.9) Macé et al 30 Mean (SD): 31.4 (4.0) Sinha et al 31 Mean: 25.0 Wei et al 32 Mean (SD): 8.8 (0.9)…”
Section: Surgical Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…ii. Approaches for handling of venous coronary flow, which drains into the RA, were analyzed and classified into two groups depending on whether the main PA was Mean (SD): 22.4 (1.5) Nawa et al 12 Mean (SD): 10.6 (1.75) Szabo et al 13 No data Szabo et al 14 Mean (SD): 22.3 (5.2) Tanoue et al 15 Mean (SD): 16.8 (2.7) Ovine Gandolfo et al 16 Range: 42.0-48.0 Koçyıldırım et al 17 Mean (SD): 65.0 (4.1) Myers et al 18 Mean (SD): 7.2 (1.1) Riemer et al 19 Range: 42.0-48.0 Rodefeld et al 20 Mean: 56.5; range: 33.0-78.6 Rodefeld et al 21 Mean (SD): 5.6 (1.5) Swartz et al 22 Mean (SD): 56.6 (5.7) Tsuda et al 23 Range: 47.0-57.0 Wang et al 24 Range: 35.0-45.0 Wang et al 25 Range: 35.0-45.0 Wang et al 26 Range: 35.0-45.0 Porcine Derk et al 27 Mean:50.7; range 44.0-61.0 Kanakis et al 28 Mean (SD): 43.0 (3.8) Klautz et al 29 Mean (SD): 28.3 (7.9) Macé et al 30 Mean (SD): 31.4 (4.0) Sinha et al 31 Mean: 25.0 Wei et al 32 Mean (SD): 8.8 (0.9)…”
Section: Surgical Classificationmentioning
confidence: 99%
“…Studies with excessive volume loading to maintain baseline levels in hemodynamics [10][11][12]30 were excluded from statistical analysis. 28 Kaku et al 10 BT Kocyildirim et al 17 Wang et al 25 Macé et al 11 CPB, VF, BT Macé et al 30 CPB, VF, BT Nawa et al 12 Szabo et al 13 Szabo et al 14 With MCS Derk et al 27,a Jarvik 2000 (Jarvik Heart Inc; New York, NY, USA)…”
Section: Hemodynamic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors observed a significant drop in coronary blood flow and left ventricular ejection fraction when the coronary sinus pressure was above 15 mmHg [42]. In 2002, Szabo et al confirmed these results with a canine TCPC model and highlighted the importance of the balance between coronary artery and coronary sinus perfusion pressures for single-ventricular function [43].…”
Section: Single-ventricle Failurementioning
confidence: 92%
“…This compensatory mechanism does not exist in the Fontan circulation and leads to decreased CO and stroke work. 13, 14 It should be emphasized that the driving force of the circulating blood volume between the systemic and pulmonary veins is the pressure gradient between central venous pressure and the left atrium (LA), assisted mechanically by the thoracic muscles and respiratory function. 5 Ventricular function and contractility in the SV patient are often depressed, thought to be because of abnormal pre-Fontan development when the ventricle is subjected to large volumes and often high pressures following PA banding, leading to ventricular hypertrophy and dilation.…”
Section: Staged Surgical Palliationmentioning
confidence: 99%